Money demand during crisis – (post) transitional perspective - Botrić, Valerija (Oeconomica Jadertina, 2017)
The existing literature on money demand in Croatia and Serbia is mostly concerned with identifying whether traditional factors are present and to what extent. The aim of this paper is to extend the traditional concept with variables that are more related to specific recent developments in analysed countries – transition and crises. Specifically, the precautionary motives for holding money are expected to be important during the crises, while financial transaction motives are expected to be important in the period before the crises. Additionally, instead of traditional cointegration approach, an ARDL testing procedure was utilized in the paper in order to avoid specific problems related to the unit root identification problems. Comparative perspective of the analysis should help to distinguish between common and specific features in the analysed countries.
Keywords: money demand; Croatia; Serbia; crisis; cointegration; ARDL